2011
DOI: 10.1016/s0140-6736(11)60701-0
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation support delivered via mobile phone text messaging (txt2stop): a single-blind, randomised trial

Abstract: SummaryBackgroundSmoking cessation programmes delivered via mobile phone text messaging show increases in self-reported quitting in the short term. We assessed the effect of an automated smoking cessation programme delivered via mobile phone text messaging on continuous abstinence, which was biochemically verified at 6 months.MethodsIn this single-blind, randomised trial, undertaken in the UK, smokers willing to make a quit attempt were randomly allocated, using an independent telephone randomisation system, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
544
5
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 695 publications
(589 citation statements)
references
References 23 publications
14
544
5
12
Order By: Relevance
“…However, it is the best estimate yet produced for the probable efficacy of text messaging used for smoking cessation in pregnancy. It is also of a similar magnitude to efficacy estimates derived from ‘definitive’ trials of similar interventions used by non‐pregnant smokers 36, 37 and to that from a smaller MiQuit trial 18. Additionally, our estimate for the probable cost‐effectiveness of the intervention is encouraging; compared with other cessation interventions, a cost‐per‐quitter of £134 is low.…”
Section: Discussionsupporting
confidence: 72%
“…However, it is the best estimate yet produced for the probable efficacy of text messaging used for smoking cessation in pregnancy. It is also of a similar magnitude to efficacy estimates derived from ‘definitive’ trials of similar interventions used by non‐pregnant smokers 36, 37 and to that from a smaller MiQuit trial 18. Additionally, our estimate for the probable cost‐effectiveness of the intervention is encouraging; compared with other cessation interventions, a cost‐per‐quitter of £134 is low.…”
Section: Discussionsupporting
confidence: 72%
“…Three interventions included text messages only [3][4][5]. One intervention included text messages and a web-based quit coach [6], while the last used text messages with links to internet videos [7].…”
Section: Resultsmentioning
confidence: 99%
“…Free et al adapted the intervention developed by Rodgers and colleagues (2009) to be delivered in the UK as a pilot study (2009) [4] and then as a full trial (2011) [5]. The findings from the small pilot study by Free et al [4] did not have significant results; however, the results from the full trial [5] demonstrated improvements in abstinence rates at the 6-month time point. Rodgers et al [3] found the same results in New Zealand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of people in high and lowmiddle income countries have mobile phones and in many of these countries text messaging services are free or nearly free to the user (OFCOM, 2009). A large UK-based trial of an intervention called 'Txt2Stop' , based on one that had previously been evaluated in New Zealand (STOMP) (Rodgers et al, 2005) has found a doubling of quit rates at six months (Free et al, 2011). The trial compared Txt2Stop with an intervention containing text messages unrelated to quitting in 5,800 smokers and analysed their effect on cessation by intention to treat.…”
Section: Introductionmentioning
confidence: 99%